Poly-ADP-ribose polymerase inhibitor use in ovarian cancer: expanding indications and novel combination strategies. Issue 5 (22nd May 2019) - Hinchcliff, Emily; Westin, Shannon Neville; Dal Molin, Graziela; LaFargue, Christopher J; Coleman, Robert L.
Abstract : The use of poly(ADP-ribose) polymerase (PARP) inhibition is transforming care for the treatment of ovarian cancer, with three different PARP inhibitors (PARPi) gaining US Food and Drug Administration approval since 2014. Given the rapidly expanding use of PARPi, this review aims to summarize the key evidence for their use and therapeutic indications. Furthermore, we provide an overview of the development of PARPi resistance and the emerging role of PARPi combination therapies, including those with anti-angiogenic and immunotherapeutic agents.